DNS Of entropy generation rates for turbulent flows subjected to high temperature gradients. (September 2021) - Avellaneda, J.M.; Bataille, F.; Toutant, A.; Flamant, G.
Highlights: DNS of the local entropy generation rate field are performed and discussed. Flow is turbulent, anisothermal, asymmetrical with thermo-dependent fluid properties. Impact of flow characteristics on local entropy generation rate statistics is studied. The characteristics and influence of thermal asymmetry are analyzed in detail. Fixing wall temperatures vs. heat fluxes strongly impacts wall turbulent fluctuations. Abstract: Direct Numerical Simulations are performed to analyze the influence of key boundary conditions and flow characteristics on entropy generation rate statistics in a highly anisothermal forced convective turbulent channel flow of a thermo-dependent fluid submitted to asymmetrical heating. Each parameter is varied separately to quantify its influence compared to a reference simulation, the hot to cold wall temperature ratio from 1.5 to 3, the mean friction Reynolds number from 150 to 210, the mean thermodynamic pressure from 1 b a r to 3 b a r . Two thermal boundary condition types are also compared (fixed temperatures vs. fixed heat flux density at the walls). For each parameter that is varied, the evolution of the entropy generation rate mean, root-mean-square and correlations with the temperature and the streamwise or wall-normal velocity components are presented and discussed. All simulations have in common the thermal asymmetry and the highly non-isothermal nature of the flow: beyond the changes induced by the variation of each parameter, the common characteristics of the statistical quantity profiles are also analyzed. This work establishes how the spatial distribution of the local entropy generation rate is modified by the parameters studied, in which direction and with which sensitivity. It demonstrates the significant influence of the thermal boundary condition type on the entropy generation rate fluctuations near the walls.